Ethical business practice and short term earning intensity during the Covid-19 crisis in Bangladesh - Khan, Md. Rahat (Goodwood Publishing, 2020)
Purpose: The central endeavor of this study is to scrutinize the standard of ethical business practice along with the intensity of short term earning on the Covid-19 crisis from a least developed country named Bangladesh. Research Methodology: The research is a concept paper based on the qualitative measurement of secondary sources of data. Results: The study urges four propositions such as, application of Golden Rule makes the businessmen’s realization regarding the suffering of consumers, Islamic Profit theory may enhance the Islamic morality and education in business practice, Building Ethical Education Curriculum may assist the ethical basement from early childhood to the whole education period which can be applicable in a real-life business career, and Trusteeship theory may rethink the businessmen about the meaning of real ownership in the natural world. Limitations: The paper is a concept paper; thus further studies have been required for practical implications based on the outcomes variables’ proof. Contribution: All the four propositions may also support the lawmakers to develop a permanent standard of ethical business climate instead of existing punitive system. Keywords: Ethical business practice, Short term earning intensity, COVID-19, Least developed country, Bangladesh